Studying structural change of suckerin protein with molecular dynamics (MD) simulations - Chen, Wenjun (2017)
Molecular Dynamic (MD) is one of the most widely used tools to explore molecular world. Mimicking a system filled with desired atoms, and inspect its structural evolution along time, we hope to further understand and test hypothesises on supramolecular structures. In recent years, a potentially new biopolymer material has been discovered from the sucker ring teeth (SRT) of squids and cuttlefishes. This SRT showed surprising properties as being thermoplastic and mechanically strong at the same time, which is rare in nature. Furthermore, SRT is found to be mostly made of modular protein polymers, unlike other robust tissues. In this project, one representative peptide of the SRT protein sequence was given special attention. We focused on its structural change when varying configurations in simulations, inspired by several structures that have been identified in natural proteins forming extensively stable networks. The role of consisting residues in stabilizing the SRT structure was also examined and will be discussed in this thesis.